Pengaruh Kualitas Produk dan Pemasaran Islami melalui WhatsApp terhadap Kepuasan Konsumen UMKM Kerupuk Ibu Tarsih - Thazra Nur Arifah; Ikhwan Hamdani; Syarifah Gustiawati (AHKAM, 2025)
Intensifying competition among UMKM (micro, small, and medium enterprises) and changing consumer behavior that demands high product quality and more ethical marketing approaches, including through digital media such as WhatsApp, require UMKM to maintain product quality while implementing marketing strategies grounded in Islamic values in order to build trust and enhance customer satisfaction. This study aimed to analyze the effect of product quality and Islamic marketing via WhatsApp on customer satisfaction of UMKM Kerupuk Ibu Tarsih in Bogor City, both partially and simultaneously. A quantitative survey design was employed, involving 61 respondents selected through incidental sampling. Data were collected using a standardized questionnaire that had been tested for validity and reliability, and were analyzed using multiple linear regression with the aid of SPSS. The results show that product quality has a significant effect on customer satisfaction, and that Islamic marketing via WhatsApp likewise makes a significant contribution to increasing satisfaction. Simultaneously, the two variables exert a strong influence, with a coefficient of determination of 0.763, indicating that 76.3% of the variance in customer satisfaction is explained by product quality and Islamic marketing via WhatsApp. These findings affirm that the combination of consistent product quality and Islamic value–based marketing communication through digital platforms is effective in building customer satisfaction and potential loyalty. The study recommends that UMKM actors consistently improve product quality and optimize Islamic marketing practices in digital media, and suggests further research to incorporate additional variables such as price and service quality as well as to extend the scope of inquiry to other UMKM contexts.